Initially, 60% of all attendees in a school party were girls. A while later, with 8 girls and 12 boys gone, the number of girls became twice as many as the number of boys. The number of people initially present was __________ .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I can't believe it was unsupervised!
Let initial number of people be x
Number of girls = 1 0 0 6 0 × x = 5 3 x
Number of boys = 1 0 0 4 0 × x = 5 2 x
Now 12 boys and 8 girls went away
New number of girls = 5 3 × x - 8 = 5 3 x − 4 0
New number of boys = 5 2 × x - 12 = 5 2 x − 6 0
Now , Number of girls = 2 x Number of boys
⇒ 5 3 x − 4 0 = 5 2 ( 2 x − 6 0 )
⇒ 3x - 40 = 2(2x -60)
⇒ 3x - 40 = 4x - 120
⇒ 4x - 3x = 120 - 40
⇒ x = 80
Therefore , the number of people initially present in the party is 8
Let x be the number of people initially at the party, B be the number of boys at the party, and G be the number of girls at the party.
From the problem,
x = B + G 0.6x = G x = 0.6x + B B = 0.4x
2(B-12) = G - 8
Since B = 0.4x and G = 0.6x, we can substitute and solve.
2(0.4x - 12) = 0.6x - 8 0.8x - 24 = 0.6x - 8 0.2x = 16
x = 80
Problem Loading...
Note Loading...
Set Loading...
Let N G and N B be the number of girls and boys at the beginning of the party, and N T = N G + N B be the number of total people.
The problem statement says that at the beginning of the party N G = 0 . 6 N T thus N B = 0 . 4 N T , which follows the following expression: N G = 2 3 N B , Eq. (1).
In a second moment, boys and girls left the party, and that can be written as N G − 8 = 2 ( N B − 1 2 ) , Eq. (2).
Substituting Eq. (1) in Eq. (2), it follows that 2 3 N B − 8 = 2 ( N B − 1 2 ) , which leads to N B = 3 2 . Using this result in Eq. (1), it follows that N G = 4 8 , so N T = 8 0 .